An Utilisation Of Machine Learning And Other Forms Of Computational Intelligence For Marketing Purposes - Dr Anwer Basha (Innovative Computing Review, 2024)
Abstract—In order to better understand how artificial intelligence may be used to aid in corporate decision making, this study will first examine previous research in this area. Artificial intelligence has the potential to reduce the quantity of human labor needed for certain tasks while increasing productivity in other areas of a business. The researcher has made an effort to apply the results of secondary data (in the form of past studies) to the functioning of the company as a whole. The repercussions will be severe for any business, but especially for large businesses operating in highly competitive areas. For certain businesses, slipping behind a rival that has used AI to improve the way they make choices might be disastrous. Since currently only minimal efforts have been undertaken for assessing the relationship between AI and the process of making strategic decisions, researchers believe that the results of this study will certainly be able to contribute something of value to the overall gamete of how artificial intelligence being applied to business